Motivasi Berprestasi dan Minat Siswa Dalam Mengikuti Ekstrakurikuler Futsal di SMP Negeri 3 Singosari - Sahal, Akhmad; Sari , Zihan Novita; Waluyo, Aprilia Yugis Tri; Abdillah, Mochamad Ilham (Universitas Singaperbangsa, 2022)
Education is one of effort which need to carried out in order to improve the learning experience. Education can be given one of them in futsal extracurricular activities. This futsal extracurricular activity can improve student achievement itself, so that high interest and motivation are very influential in student participation in futsal extracurricular activities. The purpose of this study was to find out a factual description of achievement motivation and students' interest in participating in extracurricular futsal at SMP Negeri 3 Singosari. Research design in this study is in the form of quantitative descriptive. The respondent in this study were all students who took part in the futsal extracurricular at SMP Negeri 3 Singosari. The sampling technique used is saturated sampling with a sample of 22 respondents. Data instruments were collected using a questionnaire totaling 10 motivations and 10 interests. The data analysis technique used in this research is quantitative descriptive analysis with proportions. The results of this study indicate that students' achievement motivation in the extracurricular futsal, namely 4 students (18.2%) is in the very high category, 9 students (40.9%) is in the high category, 8 students (36.4%) is in the low category, and 1 student (4.5%) is in the very low category. In addition, the results of research the students interest in futsal extracurricular found that 2 students (9%) were in the very high category, 13 students (59%) were in the high category, 6 students (27.4%) were in the low category, and 1 student was (4.6%) including very low category.